Determinants of intention to give zakat on employment income: Experience from Marawi City, Philippines. Issue 4 (8th July 2019) - Andam, Abdullah Campong; Osman, Ahmad Zamri
Abstract : Purpose: The purpose of this paper is to identify the factors influencing intention of Muslim Filipinos to give zakat on employment income. Design/methodology/approach: The study used the extended theory of planned behaviour – an extension of the theory of reasoned action – to investigate the factors influencing intention to give zakat. The theory introduces six variables (i.e. attitude, perceived behavioural control, injunctive norm, descriptive norm, moral norm and past behaviour) in predicting the intention to give zakat. Totally, 450 questionnaires were distributed to the respondents in a Muslim-majority area (i.e. Marawi City), and 384 cases were deemed usable. The data have been analysed using multiple regression analysis. Findings: This paper finds that attitude, descriptive norm and moral norm have a positive relationship with the intention to give zakat. Meanwhile, perceived behavioural control, injunctive norm and past behaviour are found to have insignificant influence over intention. However overall, the study supports the extension of the theory of planned behaviour which accounts for 53 per cent of the variance in intention. Originality/value: This paper provides new insights on factors influencing the intention to give zakat on a non-Muslim majority country setting where no zakat institution operates. This paper also used the extended theory of planned behaviour on zakat compliance literature.